The Effectiveness of Holistic Innovative Kit (Hi-Kit) in Improving Student’s Writing Skills (Borneo Engineering & Advanced Multidisciplinary International Journal, 2024)
The Fourth Industrial Revolution has brought about changes that have also affected the needs of learners. To address the needs of TVET learners in learning English, especially in writing, the Holistic Innovative Kit (Hi-Kit), an innovative teaching and learning tool, was developed. The purpose of this study is to determine how well Hi-Kit works in mixed-ability classrooms to enhance academic achievement in writing tests and students' attitudes toward learning the English language. For this action research, 41 students pursuing a diploma in tourism management were chosen. Pre-post test scores on the same topic were compared using t-tests, and the correlation between students' SPM English grades and change scores was determined using Pearson Correlation analysis. The students' attitudes about Hi-Kit being utilized in their English language classes were also obtained through the use of a questionnaire. The results indicate a noteworthy enhancement in the test scores of the students, particularly those with lower proficiency levels, and a noteworthy association between the students' SPM English grade and their test change scores. Additionally, the students' attitudes toward the use of Hi-Kit were positive. To ensure an efficient and excellent learning environment that meets the needs of diverse students in accordance with the Education Revolution 5.0, educators must be creative in integrating various teaching instructions or approaches into the classroom. As a result, this innovative teaching and learning tool, Hi-Kit, should be further promoted in other language teaching contexts.